KONSENTRASI EFFERVESCENT MIX DALAM PEMBUATAN SERBUK EFFERVESCENT EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) - Rico Andyka Harahap; Raswen Efendi; Dewi Fortuna Ayu (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Approximately ¾ part of mangosteen fruit rind is discarded as waste, while in the fruit skin there are many benefits for health as a functional food. Food that can be made from the mangosteen peel is effervescent. The effervescent drinks was favored because of practical in their preparation, quickly dissolved in water, and give sparkle effects like sodas. This study aims to get the best mix of effervescent concentration to produce effervescent powder of mangosteen rind with good characteristics. Treatments of effervescent mix in this study were 20, 25, 30, 35, and 40%. Data were analyzed by analysis of variance (ANOVA) and DNMRT at 5% level. Based on the analysis, the best treatment was effervescent mix 40% which had a solubility rate 1.57 minutes, moisture content 2.71%, ashes content 24.35%, and reducing sugar 6.67%. Sensory assessment on the best treatment was obtained yellowish brown color, slightly scented mangosteen rind, slightly sweet taste, slightly sour, slightly astringent, and overall assessment was rather preffered by panelists. Keywords:effervescent, mangosteen rind, effervescent mix